Development of application-based sepak takraw learning teaching materials android edu-touch for students at junior high school - Nurrochmah, Siti; Darmawan, Arief; ittaqwa, Ittaqwa (Universitas Riau, 2024)
(Indonesian)Tujuan pengembangan produk smartphone berupa aplikasi edu-touch pada materi pembelajaran sepak takraw sebagai bahan ajar dapat meningkatkan efektifitas dan efisiensi proses pembelajaran, Metode penelitian dan pengembangan (reseacrh & development) ini menggunakan model dan pendekatan 4d yang di kemukakan Thiagarajan, yang terdiri dari 4 tahap: analysis, design, development, implementation. Responden yang digunakan dipenelitian ini seluruhnya 6 guru PJOK dan 80 peserta didik dari dua sekolah yaitu SMPN 1 Paciran dan SMPN 1 Brondong. Instrumen yang digunakan dalam penelitian ini mengunakan angket yan disusun secara uji validitas dan reliabilitas. Persentase dari para ahli sebanyak 96% oleh ahli pembelajaran, 88% oleh ahli materi, dan 80% oleh ahli media, maka produk pengembangan valid/layak digunakan. pada uji keefektifan pada kelompok kecil dan kelompok besar diperoleh nilai 81,25% dan 79,78%, maka keefektifan produk pengembangan tergolong baik. Hasil analisis data uji kelompok kecil dan kelompok lapangan sebesar 81,25% dan 80,10%, dalam hal ini produk pengembangan termasuk dalam kategori sangat layak. Sehingga dalam penelitian ini ditarik kesimpulan sangat layak digunakan aplikasi edu-touch untuk materi sepak takraw berbasis smartphone untuk tingkat satuan pendidikan menengah pertama. (English)The objective of developing a smartphone product in the form of the Edu-Touch application for sepak takraw learning materials as teaching material is to enhance the effectiveness and efficiency of the learning process, research, and development method (research & development) this uses the 4D model and approach put forward by Thiagarajan, which consists of 4 levels: analysis, design, development, implementation. The respondents used in this research were all 6 PJOK teachers and 80 students from two schools, namely SMPN 1 Paciran and SMPN 1 Brondong. The instrument used in this research used a questionnaire which was prepared to test validity and reliability. The percentage of experts is 96% learning experts, 88% by material experts, and 80% media experts, so the development product is valid/fit for use. In the effectiveness test in small groups and large groups, the values obtained were 81.25% and 79.78%, so the effectiveness of the development product was classified as good. The results of the analysis of small group and field group test data were 81.25% and 80.10%, in this case, the development product was included in the very feasible category. So in this research the conclusion is drawn that the application is very suitable for the use of edu-touch for smartphone-based sepak takraw material for junior secondary education unit level. Copyright © The Author (s) 2024Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.